Redacción administrativa y su influencia en rendimiento de las secretarias del Municipio del cantón Vinces - Pluas Cantos, Estrella Isabel (2022)
The Municipality of Vinces is a government entity designed to plan, organize, manage and execute specific actions assigned by law for the benefit of the citizens living in said territory, its work is aimed at the social development of the Vinceño people, therefore this entity manages a high flow of documentation concerning their activities with the Municipal Government, it is then that the importance of administrative drafting in this institution itself is stipulated, which can be a determining factor in the work performance of administrative personnel, especially in professionals who work as secretaries in the said entity. For this reason, this research focuses on identifying how influential the administrative writing is in the work performance of the professionals of that municipal entity, this was achieved through various techniques and methods, starting with the description of the literature of the problem investigated until reaching the application of a survey with essential questions that help to know in greater detail the labor context of the secretaries of the municipality. Once all that information was collected that allowed us to specify a broader vision of the problem both in its theoretical and practical form, we proceeded to analyze and interpret it by applying the deductive method where the general concepts investigated were related to the work situations in the secretaries of the municipality who met through the survey. To conclude, it was obtained that these collaborators of this public entity present an unfavorable labor performance for the institution and this is due, among other things, to the incorrect execution of some important functions in their work, such as the drafting of administrative documents that they are managed internally and externally in the Municipality of Vinces.